Earliest Holocene deglaciation of the central Uummannaq Fjord system, West Greenland. (20th July 2017) - Philipps, William; Briner, Jason P.; Bennike, Ole; Schweinsberg, Avriel; Beel, Casey; Lifton, Nathaniel
Abstract : Uummannaq Fjord, West Greenland, held the Uummannaq Ice Stream system that drained an estimated 6% of the Greenland Ice Sheet (GrIS) during the Last Glacial Maximum. Published ages for the final deglaciation in Uummannaq Fjord vary from as early as c. 9.8 ka to as late as c. 5.3 ka. Assessing this variability requires additional chronological controls to improve the deglaciation history of central West Greenland. Here, we combine 14 C dating of lake sediment cores with cosmogenic 10 Be exposure dating at sites adjacent to the present GrIS margin in the central‐inland sector of the Uummannaq Fjord system. We find that ice retreated to or within the present GrIS margin at 10.8±0.2 ka (n = 6). Although this 'final deglaciation' to or within the present GrIS margin across the Uummannaq Fjord system varies from c. 10.8 to 5.3 ka, all chronologies indicate collapse from the continental shelf to the inner fjords at c. 11.0 ka, which occurred at a net retreat rate of 300–1100 m a −1 . The Uummannaq Fjord system deglaciated c. 1000 years earlier than the major fjord system to the south, Disko Bugt. However, similarly rapid retreat rates of the two palaeo‐ice stream systems suggest that their collapse may have been aided by high calving rates. The asynchronous deglaciation of the GrIS throughout the Uummannaq Fjord system probably relates to the influence of varying fjord geometry on marine glacier behaviour.